Editors’ Introduction: Understanding and Addressing Vaccine Hesitancy - Gary L. Kreps; Xuewei Chen; Ming Li (Vaccines, 2025)
The goal of this Special Issue, “Understanding and Addressing Vaccine Hesitancy”, is to examine the current state of knowledge concerning the major causes and influences of vaccine hesitancy, as well as to suggest evidence-based solutions for the growing problem of vaccine hesitancy in modern society [...]